Powering prolonged hydrothermal activity inside Enceladus - Sotin, Christophe; Postberg, Frank; Choblet, Gael; Tobie, Gabriel (Nature astronomy, 2017)
Tidal forcing within a very porous (unconsolidated) core can generate enough energy to drive all the observed global features of Enceladus. This activity can be sustained up to several billion years.
Gesehen am 05.08.2022